Textile-Based Advanced Materials Construction, Properties and Applications - Bechtold, Thomas; Manian, Avinash P. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Developments in the science and technology of textiles are not only limited to apparel and fashion. Certainly, there are research efforts aimed at improving the construction and processing of textiles for clothing-such as studies on cleaner production to reduce environmental impact, increasing the utilization of fibers and process chemicals from renewable resources, and on the recycling of materials from post-consumer waste apparel back into the manufacturing of new clothing articles. In addition, technological concepts developed for the creation of clothing over the centuries are now being investigated for use in a diverse array of fields-such as in the manufacture of engineering composites, personal protective equipment, and medicine. Further, developments in other fields-such as electronics, nanotechnology, and information and communication technologies-are being investigated for their incorporation into apparel and clothing to create "smart textiles". The aim of this Special Issue is to put together a collection of scientific reports on such efforts to highlight the range of scientific and technological issues that are being targeted and the ingenuity of the methodologies employed to find answers. It is hoped that readers of this issue will come away with an appreciation of the research being conducted in this area, and perhaps gain inspiration for their own scientific endeavors.